GEODETIC MONITORING AND MANAGEMENT OF TRANSPORT ROADS, RAILWAYS AND OTHER FACILITIES. - A.Y.Rasulov; T.T.Salaydinov (Western European Studies, 2024)
This study investigates the integration of advanced geodetic monitoring technologies—GNSS, LiDAR, UAV-based photogrammetry, and predictive analytics—for the effective management of transport infrastructure, including roads, railways, and bridges. By using high-precision, real-time data collection, the research aims to enhance early detection of structural deformations, displacement, and other hazards. The results indicate that GNSS systems can provide millimeter-level displacement measurements, while LiDAR and UAV photogrammetry offer detailed 3D models for surface deformation analysis and hard-to-reach areas inspection. Predictive analytics, powered by machine learning, enables the forecasting of maintenance needs, improving cost-efficiency and asset lifespan. The findings underscore the potential for these technologies to shift infrastructure management from reactive to proactive approaches, thus reducing operational costs, optimizing resource allocation, and extending the lifespan of critical transport infrastructure
Keywords: Geodetic monitoring; GNSS; LiDAR